Zakat issues in waqf: An exposition of shari'ah rulings - Zubaedy, Abdul Ganiyi Abdur-Raheem; Ansari, Abdul Haseeb (2016)
Generally, zakāh is the third of the five pillars of Islam and considered as a financial act of worship mandated on every Muslim who possesses al-Niṣāb. Furthermore, it is also a requirement that before zakāh can be considered obligatory on any wealth, such a wealth must be fully owned by a particular and specific owner (s). On the other hand, the usufruct and proceeds of investments generated from waqf ahlī (family waqf/specific waqf) are exclusively owned by the identified and specific beneficiaries who may be children, grandchildren, relatives or other persons specified by the wāqif (founder). Meanwhile, experience has shown that many waqf ahlī beneficiaries do not pay zakāh on their wealth that fulfills zakatability conditions as a result of lack of adequate knowledge and thus deny the poor and the needy of their economic and financial rights. This paper therefore examines the conditions for zakāh on income. It also explains the legal basis and views of different schools of laws on zakāh obligation on waqf investment proceeds with special highlight on waqf ahlī (family waqf/specific waqf) as one of the kinds of waqf established in Islam and practiced by the Companions of the Prophet (SAW). Accordingly, this paper seeks to analyze the jurisprudential (fiqhi) basis for method of calculating such zakāh while employing the concept of al-Khulṭah (combined wealth). The study adopts doctrinal legal research methodology in arriving at its conclusions and suggestions.